Enhanced thermal stability of organic solar cells comprising ternary D-D-A bulk-heterojunctions. (December 2017) - Landerer, Dominik; Mertens, Adrian; Freis, Dieter; Droll, Robert; Leonhard, Tobias; Schulz, Alexander; Bahro, Daniel; Colsmann, Alexander
Abstract Ternary absorber blends have recently been identified as promising concepts to spectrally broaden the absorption of organic bulk-heterojunction solar cells and hence to improve their power conversion efficiencies. In this work, we demonstrate that D-D-A ternary blends comprising two donor polymers and the acceptor PC61 BM can also significantly enhance the thermal stability of the solar cell. Upon harsh thermal stress at 120 °C for 2 h, the ternary solar cells show only a minor relative deterioration of 10%. Whereas the polymer/fullerene blend PTB7-Th:PC61 BM is rather unstable under these conditions, its degradation was efficiently suppressed by incorporating the near infrared-absorbing polymer PDTP–DFBT. Spectroscopic ellipsometry investigations and an effective medium analysis of the ternary absorber blend revealed that the domain conformation in presence of PDTP–DFBT remains stable whereas the domain conformation changes in its absence. The ternary PTB7-Th:PDTP–DFBT:PC61 BM solar cells yield thermally stable power conversion efficiencies of up to 6%. Organic solar cells: Polymer mixtures enhance the thermal stability Organic solar cells increase their lifetime by adding another polymer component, paving the way towards commercialization. A team led by Alexander Colsmann at Karlsruhe Institute of Technology, Germany conducted systematic spectroscopic investigations and device characterizations to demonstrate that the degradation of PTB7-Th: PC61 BM solar cell can be efficiently suppressed by incorporating the near infrared-absorbing polymer PDTP-DFBT. Upon harsh thermal stress at 120 °C for 2 h, the ternary solar cells show only a minor relative deterioration of 10% with a high power conversion efficiency of 6%. This work reveals the importance of a third component to lock the phase conformation of the polymer and fullerene domains. This is a key step for the thermally stable power output thus the commercialization of the organic solar cells.